2018
DOI: 10.1016/j.joca.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Initial tissue repair predicts long-term clinical success of knee joint distraction as treatment for knee osteoarthritis

Abstract: KJD shows long-lasting clinical and structural improvement. In addition to a greater survival rate for males (>two out of three), the initial cartilage repair activity appears to be important for long-term clinical success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 16 publications
3
58
0
Order By: Relevance
“…The maximal effect regarding clinical benefit and structural repair has in all trials been obtained around one-year follow-up, sustaining for many years thereafter. [10,11] Therefore the one-year follow-up comparison with regular care outcome is considered predictive of the long-term outcome in regular care. Nevertheless, longer follow-up in regular care with larger number of patients is still warranted to proof this assumption.…”
Section: δWomac Mean (95%ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…The maximal effect regarding clinical benefit and structural repair has in all trials been obtained around one-year follow-up, sustaining for many years thereafter. [10,11] Therefore the one-year follow-up comparison with regular care outcome is considered predictive of the long-term outcome in regular care. Nevertheless, longer follow-up in regular care with larger number of patients is still warranted to proof this assumption.…”
Section: δWomac Mean (95%ci)mentioning
confidence: 99%
“…In over three quarters of the patients, TKA could be postponed for over five years, and half of the patients was still without prosthesis nine years after treatment. [8][9][10][11] After this trial the distraction period was shortened to six weeks, as this was considered sufficient. [12] Between 2011 and 2014, the six-week KJD was studied in comparison to TKA or to high tibial osteotomy (HTO) in two separate randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 3 were excluded, since they reported on a subgroup from other included articles without reporting extra information on primary outcomes, leaving 11 articles included for analysis. [12][13][14][15][16][17][18][19][20][21][22] As multiple articles reported on different follow-up moments in the same patient cohorts, the overview of selected studies is separated per cohort of KJD-treated patients and control groups ( Table 1). 23 A total of 7 patient cohorts were treated with KJD, of which 2 in combination with another treatment: 1 cohort of 6 patients was treated with KJD and microfracture 13 and 1 cohort of 19 patients treated with KJD, microfracture, and debridement 15 that also had a control group of 42 patients treated with microfracture and debridement alone.…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies of joint distraction have shown sustained and clinically significant improvement at a number of joint sites 13,14 . For knee OA, joint distraction improved knee symptoms for 5e9 years in individuals with established OA 15,16 . Remarkably, the 6 week intervention also led to apparent cartilage regeneration in the subsequent months and years, with increase in joint space width on X-ray, and increased articular cartilage thickness on magnetic resonance imaging (MRI) 14,16e18 .…”
Section: Introductionmentioning
confidence: 99%